Rethinking the creative power of God - Muis, Jan (HTS teologiese studies, 2016)
Because the notion of ‘power’, and of ‘absolute power’ in particular, is associated with coercion, violence and oppression, it is problematic to attribute power to God. Jürgen Moltmann and Eberhard Jüngel reject a ‘theistic’, ‘metaphysical’ concept of God’s ‘absolute power’ and highlight the powerlessness of the suffering and dying God on the cross. In their view, limitation of power is also central to God’s creative power. In this article, this kenotic view on God’s creative power is examined. Firstly, the political philosophy of Thomas Hobbes is explored as an important and still influential source of the modern view on absolute power as dominion. Next, it is discussed whether the innovative view on divine, creative power of Sören Kierkegaard can be seen as kenotic. Because both Hobbes and Kierkegaard refer indirectly to the classical distinction between potentia absoluta and potentia ordinata, this distinction, and its rejection by Schleiermacher, is investigated. The article concludes by proposing ‘empowering power’ as a non-oppressive and non-kenotic view on God’s creative power.